Controllable single-photon routing between two waveguides by two giant two-level atoms - Zhang, Y. Q.; Zhu, Z. H.; Chen, K. K.; Peng, Z. H.; Yin, W. J.; Yang, Y.; Zhao, Y. Q.; Lu, Z. Y.; Chai, Y. F.; Xiong, Z. Z.; Tan, L. (Frontiers in Physics, 2022)
We investigate the single-photon quantum routing composed of two infinite waveguides coupled to two giant two-level atoms. The exact expressions of the single-photon transmission and reflection amplitudes are derived with the real-space approach. It is found that the single photon scattering behavior is strongly dependent on the phase difference between the two adjacent atom-waveguide coupling points, the frequency detuning, the coupling strength between the two giant atoms, and the interaction strengths between the giant atoms and the waveguides. Our studies show that an ideal single photon router with unit efficiency can be realised by designing the size of the giant atom, and the frequency detuning or adjusting the interaction strengths between the atoms and the waveguides. The results suggest the potential to effectively control the single-photon quantum routing based on the giant-atom setup.